Hyperuricemia from A to Z - article Editorial (Евразийский Кардиологический Журнал)
An online scientific summit “Hyperuricemia from A to Z” supported by EGIS-RUS LLC was held on December 4, 2021.The following experts of the Russian Medical Society on Arterial Hypertension (RMSAH) were the speakers and facilitators of the summit: Kislyak O.A., Zhernakova Yu.V., Mironova O.Yu., Blinova N.V., headed by the President of the RMSAH Chazova I.E. as well as a special guest from Italy, Claudio Borghi, Professor, Head of the Department of Cardiovascular Diseases of the University of Bologna. More than 50 experts in the cardiology area from different regions of Russia participated in the summit.Relevance of the topic is confirmed by the proved association between hyperuricemia cardiovascular mortality.